2021
DOI: 10.1016/j.csbj.2021.03.025
|View full text |Cite
|
Sign up to set email alerts
|

Neuropilins: C-end rule peptides and their association with nociception and COVID-19

Abstract: Graphical abstract Binding of the SARS-CoV-2 S1 CendR peptide to neuropilin-1 aids host invasion, while the binding of the VEGF-A 164 CendR peptide is associated with nociception.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 33 publications
0
18
0
3
Order By: Relevance
“…Indeed, through its exposed C-end rule (CendR) motif following the furin processing, the SARS-CoV-2 spike protein binds to the NRP1 CendR pocket, which allows it to achieve endocytosis and cell entry. This binding interferes with that of NRP1's endogenous ligand VEGF-A, a signaling that would otherwise promote nociception [21]. The ensuing silencing of pain through the VEGF-A pathway may underlie increased disease transmission in asymptomatic individuals [22].…”
Section: The Less Well-known Nrp-1 Role and Its Remarkable Potentialmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, through its exposed C-end rule (CendR) motif following the furin processing, the SARS-CoV-2 spike protein binds to the NRP1 CendR pocket, which allows it to achieve endocytosis and cell entry. This binding interferes with that of NRP1's endogenous ligand VEGF-A, a signaling that would otherwise promote nociception [21]. The ensuing silencing of pain through the VEGF-A pathway may underlie increased disease transmission in asymptomatic individuals [22].…”
Section: The Less Well-known Nrp-1 Role and Its Remarkable Potentialmentioning
confidence: 99%
“…Hence, this NRP1 binding could stimulate the separation of S1 and S2 domains, which will probably increase the infectivity of SARS-CoV-2 as the liberated S2 mediates the fusion of the virus and other host membranes [23]. As such, NRP1 may increase viral infection by SARS-CoV-2 in the presence of other host factors like ACE2 [21], and it may also initiate receptor-dependent viral internalization, potentiate severe immune-pathological inflammation, and lead to a systemic spread of the infection [8], independently of ACE2. Nonetheless, recent in-vitro studies are showing that NRP1 alone did not increase cell susceptibility to viral infectivity [24], suggesting that it may enhance viral infectivity via other host factors, rather than mediate it itself.…”
Section: The Less Well-known Nrp-1 Role and Its Remarkable Potentialmentioning
confidence: 99%
“…NRP-1 is implicated in several aspects of a SARS-CoV-2 infection, including possible spread through the olfactory bulb and into the central nervous system and increased NRP-1 RNA expression in lungs of severe COVID-19 [54]. Moreover, NRP-1 may also serve as an immune checkpoint of the memory T cell in COVID-19 [55]. It has been identified that binding of the SARS-CoV-2 spike protein to the NRP-1 receptors impacts the docking of the VEGF-A ligand [55].…”
Section: Sites Of Sars-cov-2 Invasionmentioning
confidence: 99%
“…Moreover, NRP-1 may also serve as an immune checkpoint of the memory T cell in COVID-19 [55]. It has been identified that binding of the SARS-CoV-2 spike protein to the NRP-1 receptors impacts the docking of the VEGF-A ligand [55]. NRP-1 may act as a host cell mediator that is able to increase the infectivity of the virus and thus contribute to the tropism of the coronavirus [56].…”
Section: Sites Of Sars-cov-2 Invasionmentioning
confidence: 99%
“…NRP-1 is a membrane-bound co-receptor to a tyrosine kinase receptor for both vascular endothelial growth factor and semaphorin family members. Recently, NRP-1 has been identified as a possible novel factor for SARS-CoV-2 host cell entry [103]. After cleaving by furin, S1 and S2 proteins are exposed.…”
Section: Neuropilin-1mentioning
confidence: 99%